Never say dye: New roles for an old fluorochrome - Fotopoulos, Vasileios (My University, 2012)
Recent years have seen a remarkable increase in the number of publications dealing with the application of epifluorescence microscopy in cell biology. This can be widely attributed to the development of state-of-the-art image processing programs, as well as the development of new reagents/probes, which allow the labeling of most cell structures, organelles and metabolites with high specificity. However, the use of a specific fluorescent dye, 3,3'-dihexyloxacarbocyanine iodide (DiOC 6), has been recently revisited and several new application potentials have emerged. The goal of this mini-review is to provide an up-to-date overview of the multiple roles of this multifaceted probe
Keywords: Fluorescence microscopy; Biology; Metabolites